Tolerance to the antinociceptive effects of chronic morphine requires c-Jun N-terminal kinase - Marcus, David J. (Mol Pain, 2015)
BACKGROUND: Morphine and fentanyl are opioid analgesics in wide clinical use that act through the μ-opioid receptor (MOR). However, one limitation of their long-term effectiveness is the development of tolerance. Receptor desensitization has been proposed as a putative mechanism driving tolerance to G protein-coupled receptor (GPCR) agonists. Recent studies have found that tolerance to morphine is mediated by the c-Jun N-terminal Kinase (JNK) signaling pathway. The goal of the present study was to test the hypotheses that: 1) JNK inhibition will be antinociceptive on its own; 2) JNK inhibition will augment morphine antinociception and; 3) JNK mediates chronic tolerance for the antinociceptive effects of morphine using acute (hotplate and tail-flick), inflammatory (10 μl of formalin 2.5 %) and chemotherapy (cisplatin 5 mg/kg ip once weekly)-induced neuropathic pain assays. RESULTS: We found that JNK inhibition by SP600125 (3 mg/kg) produces a greater antinociceptive effect than morphine (6 mg/kg) alone in the formalin test. Moreover, co-administration of morphine (6 mg/kg) with SP600125 (3 mg/kg) produced a sub-additive antinociceptive effect in the formalin test. We also show that pre-treatment with SP600125 (3 or 10 mg/kg), attenuates tolerance to the antinociceptive effects of morphine (10 mg/kg), but not fentanyl (0.3 mg/kg), in the tail-flick and hotplate tests. Pre-treatment with SP600125 also attenuates tolerance to the hypothermic effects of both morphine and fentanyl. We also examined the role of JNK in morphine tolerance in a cisplatin-induced model of neuropathic pain. Interestingly, treatment with SP600125 (3 mg/kg) alone attenuated mechanical and cold allodynia in a chemotherapy-induced pain model using cisplatin. Strikingly, SP600125 (3 mg/kg) pre-treatment prolonged the anti-allodynic effect of morphine by several days (5 and 7 days for mechanical and cold, respectively). CONCLUSIONS: These results demonstrate that JNK signaling plays a crucial role in mediating antinociception as well as chronic tolerance to the antinociceptive effects of morphine in acute, inflammatory, and neuropathic pain states. Thus, inhibition of JNK signaling pathway, via SP600125, represents an efficacious pharmacological approach to delay tolerance to the antinociceptive effects of chronic morphine in diverse pain models.